Pengaruh Promosi dan Kualitas Produk terhadap Keputusan Pembelian Banten pada Griya Upakara Bali - Pramana, Ida Bagus Oka Yudi (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purpose of this study was to determine the impact of advertising and product quality on consumer purchasing decisions at Griya Upakala Bali, Denpasar. The population used in this study was a sample of 85 respondents in total who were Griya Upakala Bali consumers who made two or more purchases and were identified using targeted sampling methods. Data were collected through observations, interviews, documentation, literature searches, and questionnaires. The data analysis technique used in this study is the multiple regression analysis technique. Based on the research results, we can say: Promotions and product quality have a partial, positive and significant impact on purchasing decisions at Griya Upakara Bali. Given these results, Griya Upakara Bali will be conducting more advertising through social media in the future to increase consumer purchasing decisions and to make it easier for consumers to find information about the products that Griya Upakara Bali sells. You have to be proactive.